Ring stage dormancy of Plasmodium falciparum tolerant to artemisinin and its analogues – A genetically regulated “Sleeping Beauty” - Auparakkitanon S. (2023)
The appearance in 2008 in western Cambodia of Plasmodium falciparum tolerant to artemisinin, defined by longer parasite clearance time following drug administration and in vitro by a slightly higher survival rate of the ring stage after a 3-h treatment with 700 nM artemisinin (or analogues, collectively termed ART), has raised concerns of the possible loss of this frontline antimalarial [used in the form of an artemisinin combination therapy (ACT)], with its low IC50 value against the ring stage and pleiotropic pro-drug/poison property. The key genetic marker of ART tolerance phenotype is a number of non-synonymous mutations in Pfkelch13 propeller domain. This results in defective assembly at the ring stage of a cytostome structure located at cytoplasmic side of the parasite membrane required for invagination of a double-membrane endosome carrying host cytosol haemoglobin to the digestive vacuole. The consequential deprivation of amino acids initiates ring stage parasites bearing the causal mutations in PfK13 (or other key cytostome components) entry into a dormant state (“Sleeping Beauty”), which, after a duration longer than that the short-lived ART, “Sleeping Beauty” ring parasite resumes its normal, but accelerated, development to maintain the 48-h intra-erythrocytic life-cycle. We posit that when ART-tolerant P. falciparum has acquired under ART stress the causative PfK13 mutation (not obligatory if mutations occur in other critical cytostome components), together with other necessary mutations to adjust to the new normalcy and to provide survival competitiveness, ART-tolerant parasite has now evolved into a genetically programmed “Sleeping Beauty”. The onus of preventing the spread of ART-tolerant P. falciparum lies with the efficacy of ACT partner drug, hence the recommendation of a triple ACT (TACT). Nevertheless, attention should also be focussed on understanding the mechanisms of dormancy, such as induction, maintenance and recovery, to enable discovery and development of novel antimalarials targeting this unique parasite stage.